Market intervention and easing the shortage of sugar (a case study in Muar) / Qurratu ‘Aini Sabtu - Sabtu, Qurratu ‘aini (2010)
Crisis of sugar is a social problem that can result in daily life people in terms of the interference cost and increase daily, if not addressed or dealt with promptly and effectively it will affect the economy. This study was done to identify the total amount production of sugar per month produced by Manufacturer (MSM and CSR), to identify the total amount provided by each wholesaler to Supermarket (The Store Muar, Econsave, Astaka, The Store Tangkak, Giant and Fresco. Besides that, review and analyze which factor (buying sugar in large quantities, storing an out of ordinary reserve stock, increment of demand during festive season, smuggling, and insufficient transport) and to analyze whether all factor will contribute to the crisis of shortage of sugar. Thus, this study is to communicate the rationale and recommendations for addressing problems of this crisis and avoid the crisis from recur against. Base on the comparison between the quota that were given and the distribution of the sugar supply. Firstly, the quota that distributing from manufacturers to wholesalers is difference. Firstly the stock of sugar receives for every month sometime more than the quota provided. It is because of the stock received for the previous month. So the wholesaler can carry on the balance of stock of sugar to the next month. Next, consecutively month those get the surplus of stock. It is because in that month the consumption of the sugar by the consumers is surplus causes of festive occasion. Second is base on the stock of sugar in supermarket. Some time the sugars are shortage in the supermarket. This is due to the factor of shortage of transport by the wholesalers. Before the crisis shortage of sugar supplies, wholesalers typically received stock delivery sent twice a month. But after the occurrence of the shortage of sugar supplies, wholesalers had to meet market demand by making the delivery of supplies once a week. By way of delivery once a week, wholesalers were lack of transport to enable immediate delivery of the run. Therefore, the actions of the supermarket are not to cooperate in addressing this issue also invite the lack of sugar supply in the market. But again, there still a problem when some supermarket cannot provide cash due to control of cash flow by their head quarter. Third is base on the consumption of the sugar by year. It is increase every year. It is because of the demand from the consumer are high. The increasing of the consumption of sugar is starting from year 1991 until 1997. But the next year, the consumption of the sugar was decrease. It is because of the sugar supplies are down causes of the flooding, the sugar cane farm were suffered damage and shortage of production by manufacturer. Other then that, the factor contribute to the decreasing is when the shortage of production by manufacturer occurred, the sugar supply in the market are also face shortage. So the customer cannot use the sugar. Lastly, the reason of the decreasing of the consumption is the smuggling activities and insufficient transportation to distribute the sugar supply by wholesaler to the supermarkets. This analysis use various researches to obtain secondary data sources that are useful and help researcher prepare this study. By the way, this study expected to be used by various parties who wish to refer to assist in decision-making process and take appropriate action so that problems can be solve effectively.